The Accessibility Level of Cigudeg Village as Prospective Capital City of West Bogor Regency - Trenggana, Soma (International Journal of Environment, Agriculture and Biotechnology, 2019)
This article contains a spatial review concerning the appointment of Cigudeg Village as a candidate of the capital city of Bogor Barat Regency. Bogor Barat Regency is one the regencies are being proposed to be a new regency in West Java Province. This research aimed to determine the feasibility of Cigudeg Village as the capital city candidate from the spatial accessibility point of view. The research begun by proposing other locations instead of Cigudeg Village as a comparison. The selection of village candidates was based on 3 scenarios: (1) all villages in Cigudeg District were deserved to be chosen as the capital city candidates; (2) all villages within the Bogor Barat Regency were deserved to be selected as the capital city candidates; (3) a centroid of Bogor Barat Regency was deserved to be included in the selection of the capital city of Bogor Barat Regency. The analysis of location-allocation weighted by the total population per district, was used to obtain the chosen village based on the above scenarios. The analysis resulted in three different chosen villages, that are Cigudeg (scenario 1), Leuwiliang (scenario 2) and Bayuresmi 2 (scenario 3). A comparative analysis then carried out to choose which village among those three that actually has a highest value of accessibility. Travel distance, travel time, and public transportation cost used a base of comparative analysis. The result of comparative analysis shows that Leuwiliang Village has the highest accessibility level, followed by Cigudeg and Bayuresmi 2 on the third place.